ANALISIS HASIL PEMBELAJARAN MATEMATIKA PADA MATERI MEMBACA JAM DAN SELISIH WAKTU MELALUI EVALUASI POST-TEST DI SD NEGERI 5 DOOM: ANALYSIS OF MATHEMATICS LEARNING OUTCOMES ON THE MATERIAL OF READING CLOCK AND TIME DIFFERENCE THROUGH POST-TEST EVALUATION AT STATE ELEMENTARY SCHOOL 5 DOOM - Musa'ad, Faida; Musa'ad, Faija; Latifah, Ummu Wachidatul; Sarira, Regina Amelia; Mafinanik, Ajima (Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze student learning outcomes in the material of reading the clock and calculating time differences through post-test evaluation at SD Negeri 5 Doom. Using a descriptive quantitative approach, this study involved grade III A students selected by purposive sampling. The post-test results showed an average student score of, with only students achieving the Minimum Completion Criteria (KKM) of 70. Low-ability students had difficulty in reading the position of the clock hands and converting time units, while medium-ability students had difficulty with more complex problems, and high-ability students were able to solve the problems correctly. The main factors that influenced learning outcomes were the abstract nature of the time material, the minimal use of visual media, and a suboptimal learning approach. Based on these findings, it is recommended to increase the use of visual media such as manipulative clocks or digital applications, provide gradual exercises, and provide special assistance for students with low abilities to improve student understanding and learning outcomes.